Five on a treasure island (The famous five) - Blyton,Enid (London: Hodder children's books, 2010)
It's Julian, Dick and Anne's first visit to Kirrin to meet their cousin George - never call her Georgina! - and her loyal dog Timmy. Exploring together, they discover the location of some ancient family treasure marked on a hidden map. They must work quickly to find it as they are not the only ones searching for it
Keywords: English, Fiction